Estudo do processo de criação da obra "Os voluntários", de Moacyr Scliar, e a temática judaica - Freitas, Cibele Beirith Figueiredo (2015)
This thesis has as its corpus the typescripts of the novel Os voluntários, by Moacyr Scliar, based on the genetic critcism's theoretical foundations. For this study, two typed versions of the literary work were collated and the main increases found in the comparison of the first with the second typed version were analysed. This research sought to demonstrate that most of the additions and the epigraphs inserted by the writer during the creative process, deal with jewish themes, arising from Moacyr Scliar's cultural and historical heritage